2017
DOI: 10.7249/rr1694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Housing for Health Permanent Supportive Housing Program

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 20 publications
4
33
0
3
Order By: Relevance
“…Given that 95% of the sample was stably housed at the 12‐month follow‐up, this may suggest that housing itself is a facilitator of positive changes in mental health symptomatology for formerly homeless adults. These findings are consistent with a recent PSH evaluation study of Los Angeles‐based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, ) and two studies of Canadian‐based PSH residents that found mental health improved in housing (Chung et al, ; Gadermann et al, ). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Given that 95% of the sample was stably housed at the 12‐month follow‐up, this may suggest that housing itself is a facilitator of positive changes in mental health symptomatology for formerly homeless adults. These findings are consistent with a recent PSH evaluation study of Los Angeles‐based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, ) and two studies of Canadian‐based PSH residents that found mental health improved in housing (Chung et al, ; Gadermann et al, ). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionsupporting
confidence: 88%
“…Angeles-based adults experiencing homelessness with complex medical and behavioral conditions (Hunter et al, 2017) and two studies of Canadian-based PSH residents that found mental health improved in housing (Chung et al, 2018;Gadermann et al, 2015). Housing may be associated with mental health improvements by virtue of a number of mediating factors, including a sense of security and stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 19 studies assessing the cost and net cost of housing interventions. 30,41,45,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145] In some studies, permanent supportive housing interventions were associated with increased cost to the payers, and the costs of the interventions were only partially offset by savings in medical and social services as a result of the intervention. 30,41,[131][132][133][134]142 Six studies showed that these interventions saved payers money.…”
Section: Permanent Supportive Housingmentioning
confidence: 99%
“…30,41,[131][132][133][134]142 Six studies showed that these interventions saved payers money. 135,137,139,141,144,145 Four of these studies, however, employed a pre-post design. 135,139,141,145 Moreover, 1 cost-utility analysis of PSH suggested that the provision of housing services was associated with increased costs and increased quality-adjusted life years, with an incremental cost-effectiveness ratio of US$62 493 per quality-adjusted life year.…”
Section: Permanent Supportive Housingmentioning
confidence: 99%